Opini Terkini Tentang Dinding Sel Tanaman: Struktur, Biosintesis, dan Aplikasinya - Dina Yulia; Bintarti Yusriana (Universitas Atma Jaya Yogyakarta, 2006)
Plant cell walls are unique, complex, diverse and dynamic structures that change throughout the process of cell division, growth and differentiation. Plant cell walls are not only a single key determinant of overall plant form, but they also play an important role in sustaining human societies. Evidence of how cell walls are crucial for plant structure is that without cell walls, plants would be elastic piles of protoplasm, more like slime moulds than stately trees. Unlike animals, in which specialized skeletal system provides physical support, the strength, flexibility, texture and overall shape of higher plants depend on the cumulative properties of walls. Moreover, plants are composed of approximately 35-40 cell types that are distinguished from each other by the chemistry and organization of their walls. In human societies, cell walls directly affect the quality of most plant-based products, including paper and pulping, textile, food quality and texture, dietary fibre, malting and brewing and bioethanol production (Cosgrove, 2005; Farrokhi et al., 2006).The chemical structure of most wall components has been intensively studied and defined in detail, however, the enzymes responsible for cell wall biosynthesis and also its restructure remain poorly understood. However, currently, there has been real progress towards understanding the cell wall biosynthesis, using various emerging approaches, such as genetic and biochemical approaches (Farrokhi et al., 2006).This review will elaborate on recent advances in our knowledge of the structure cell walls of flowering plants, particularly the structure of primary cell walls. Moreover, this review will also explain the current knowledge towards understanding primary wall biosynthesis and also the future application of cell wall study in biotechnology.